'We have just entered the Wright Brothers phase of the digital era': data management and practice in the eResearch era - Weaver, B; Henty, M (2008)
While supercomputing facilities and high speed internet connections are crucial components for successful eResearch, also important are academic culture, institutional capabilities and individual skills if we are to optimise our potential. In the second half of 2007, three Australian universities conducted surveys of data management practices among their researchers and followed these up with more detailed investigations. The consistency of results suggests not only that researchers share many common practices and attitudes, but that the hurdles they encounter are also common. Overall, the surveys showed that researchers are more focussed on research outcomes than on good research management practices, especially when it comes to the long term stewardship of data.